Sublating Sinic relationism - Rošker, Jana S. (Asian studies, 2022)
This paper aims to bring into the global ethics debate concrete alternative models of specific relational ethics developed in the context of Sinic traditions that have not yet been widely introduced into Western scholarship or integrated into the framework of global discourses on ethics and morality. Although much research has been done on certain elements and aspects of such ethical models, there have been no concrete attempts to incorporate them into a global axiological framework that could have helped humanity develop strategies for solving the current global crises we face. The paper first provides a critical overview of the conceptual history, specific characteristics, and social relevance of relationism. It then addresses the question of how relational ethical models could be integrated into the value system of contemporary global ethics without reproducing the still dominant normativity of Western epistemology and its corresponding axiology. After highlighting some problems related to the methodology and structure of traditional models of comparative philosophy and ethics, the author suggests that this integration of relationism into the general framework of global ethics could be done by applying a new method, which can be tentatively called the method of transcultural philosophical sublation. Starting from different frames of reference that define the basic tenets of modern Western and traditional Chinese axiology, the author demonstrates the application of this method on the example of different conceptions of the human self.
Keywords: Chinese philosophy; kitajska filozofija; post-comparative philosophy; postprimerjalna filozofija; primerjalna filozofija; Ruism; Ruist role-ethics; ruistična etika vlog; ruizem; Sinic relationism; siniška odnosnost; sublacija; sublation; transcultural ethics; transkulturna etika